Role of bioaerosol in virus transmission and material‐based countermeasures. Issue 6 (23rd May 2022) - Joseph, John; Baby, Helna Mary; Zhao, Spencer; Li, Xiang‐Ling; Cheung, Krisco‐Cheuk; Swain, Kabir; Agus, Eli; Ranganathan, Sruthi; Gao, Jingjing; Luo, James N; Joshi, Nitin
Abstract: Respiratory pathogens transmit primarily through particles such as droplets and aerosols. Although often overlooked, the resuspension of settled droplets is also a key facilitator of disease transmission. In this review, we discuss the three main mechanisms of aerosol generation: direct generation such as coughing and sneezing, indirect generation such as medical procedures, and resuspension of settled droplets and aerosols. The size of particles and environmental factors influence their airborne lifetime and ability to cause infection. Specifically, humidity and temperature are key factors controlling the evaporation of suspended droplets, consequently affecting the duration in which particles remain airborne. We also suggest material‐based approaches for effective prevention of disease transmission. These approaches include electrostatically charged virucidal agents and surface coatings, which have been shown to be highly effective in deactivating and reducing resuspension of pathogen‐laden aerosols. Abstract : Virus dissemination through droplets or aerosols is a predominant transmission mode of respiratory infections. This review summarizes direct and indirect mechanisms of aerosol generation with an emphasis on infection risks presented by the resuspension of settled droplets. Material‐based approaches, including nanotechnology, to contain bioaerosol‐mediated virus transmission are highlighted in this review.